Analysis of Scoliosis-related Medical Services in South Korea Between 2010 and 2018: A Cross-sectional Study Using Health Insurance Review and Assessment Service Data. Issue 12 (15th June 2022) - Hong, Doohyun; Lim, Yu-Cheol; Lee, Sook-Hyun; Sung, Won-Suk; Lee, Yoon Jae; Kim, Eun-Jung; Ha, In-Hyuk
Abstract : This study retrospectively analyzed HIRA-NPS data for scoliosis patients between 2010–2018. Patients aged ≤24 years were most frequently treated for scoliosis, most patients were outpatients, and conservative treatments were relatively more common. The findings can serve as foundational data for healthcare policymakers, clinicians, and researchers. Abstract : Study Design: Retrospective, cross-sectional study. Objectives: The aim of this study was to analyze types and cost of care for scoliosis and present health care utilization by patients to provide data on the standard treatment and cost for scoliosis in South Korea. Summary of Background Data: Scoliosis is defined as an abnormally laterally curved spine with a Cobb angle of ≥10°.Data are lacking on which treatments are popular for general scoliosis and which service categories incur the most cost in South Korea. Methods: Data from the Health Insurance Review and Assessment Service-National Patient Sample were used. In total, 108, 643 final cases and 32, 362 patients in South Korea who received Western medicine care or Korean medicine care at least once with scoliosis (ICD-10 code M41) as the principal diagnosis during January 2010 to December 2018 comprised the study sample. We analyzed health care utilization according to certain factors (e.g., age, sex, payer type, type of visit, and medical institution), health care utilization by service category and service code, and medication prescriptions filled by private or hospital pharmacies. Results: Patients aged 24 years or younger most frequently utilized health care services, with more female (64.84%) than male patients (35.16%). Most patients received only Western medicine care (92.18%), whereas 6.56% only received Korean medicine care. Most cases (99.37%) corresponded to outpatient. Regarding service category, treatment and surgery, examination, special equipment and radiologic diagnosis accounted for a substantial percentage. Regarding service code, cost of examination, imaging, and physiotherapy comprised a high percentage of Western medicine, whereas cost of examination, acupuncture, and cupping therapy accounted for a high percentage of Korean medicine. The most commonly prescribed medications for scoliosis in pharmacies were anti-inflammatory analgesics (nonsteroidal anti-inflammatory drugs), antacids, and skeletal muscle relaxers. Conclusion: The findings can be used as foundational data for experts such as health care policymakers, clinicians, and researchers. Level of Evidence: 4